Orquestra Brasileira de Minas Gerais: Projeto TIM Música nas escolas - Marilena Consuelo Horta de Melo Popoff (2011)
This dissertation addresses the implementation of the TIM Music Project in the Schools. There are two public schools concerned, the State Public School Father John Botelho and Francisco Bicalho, both in the district of Barreiro, in Belo Horizonte, MG. The development of this dissertation is based in the social impact caused by this project with the formation of its Brazilian Orchestra of Minas Gerais.The social impact caused by this project through the formation of its Brazilian Orchestra of Minas Gerais is the base of the development of this dissertation. The theoretical of the 'Culture of Peace UNESCO' guided the project as a guideline for all decision-making within the context of educational and musical activity, from the simplest to the most complex. The four pillars of contemporary education the Delors Report "learn to be", "learning to do," "learn to live together" and "learning to know" are the axes of this work. The qualitative research approach enabled the production of descriptive data and the option to use the semi-structured interviews as the main instrument for data collection, always with the interest of thinking about music as important discipline in the school curriculum for children and adolescents.